STAGE: an Integrated Environment for Statistical Test Script Generation - Copstein, Bernardo; Oliveira, Flávio; Reginato, Lucas R. C. (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2004: Anais do V Workshop de Testes e Tolerância a Falhas, 2004)
This work describes STAGE, an integrated environment for statistical test case generation and scripting, developed at the CPTS (Software Testing Research Center). The key contributions of the system are the use of stochastic automata networks (SANs) for representing the usage model and an intermediate model (called the Interface Event-State Model) to map the abstract usage model into the implemented interface components. SANs allow modular representation of systems with complex non-deterministic behavior, minimizing the state-space explosion found in Markov chains. The use of a separate model for the implementation has the advantage of making changes in the interface and generating the script automatically without affecting the abstract usage model. We implemented the technique into the STAGE environment; the experiments indicate that the performance of test case and script generation with SANs is at least compatible with Markov-based generation.